Waste heat from a portable combustion unit (PCU) for a thermoacoustic heat engine - Normah Mohd. Ghazali, 1961- 544369; Azhar Abdul Aziz, 1959- 378745; International Conference on Thermal Engineering (2nd : 2004 : Dhaka, India) 481860 (Skudai : Universiti Teknologi Malaysia, 2004)
19